Gender-Role Stereotypes in Integrated Social Marketing Communication: Influence on Attitudes towards the Ad. Issue 3 (August 2013) - Robertson, Kirsten; Davidson, Jessica
This study examines the influence of stereotyped gender-role depictions on attitudes towards integrated social marketing communication (ISMC) through an application of Gender-Role Theory and the Stereotype Content Model. One hundred and seventy five participants completed surveys measuring their cognitive and affective attitudes towards four advertisements that varied in gender-role congruency (congruent/incongruent) and stereotype content (paternalistic/contemptuous). The advertisements targeted male perpetrated partner violence (congruent/contemptuous); female perpetrated partner violence (incongruent/contemptuous); regretful sex experienced by a female (congruent/paternalistic); and regretful sex experienced by a male (incongruent/paternalistic). Findings revealed cognitive attitudes were more favorable when the gender of the depicted character and target behavior were consistent with gender-role stereotypes. Affective attitudes varied as a function of stereotype content. Participants' affective attitudes were more favorable towards advertisements depicting paternalistic behavior compared to contemptuous behavior. The findings question the role of affective attitudes in evaluating ISMC advertisements and raise ethical questions regarding social marketing.